2010
DOI: 10.1080/15287394.2010.485067
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation at a Metallothionein2APromoter Single-Nucleotide Polymorphism in White and Black Females in Midwestern United States

Abstract: Genetic variation leading to differences in expression and regulation of metallothionein proteins may contribute to observed differences among individuals in terms of cadmium (Cd) uptake and metabolism. The aim of this study was to determine the frequency of the A and G alleles at rs28366003, which lies in the 5' promoter region of MT2A, in White and Black females in the Midwestern United States. One-milliliter saliva samples were collected from 298 White or Black adult female volunteers, and DNA was isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Our recent study has also reported a similar prevalence of A by G replacement at position −5 in the core region of the MT2A promoter for homozygous common allele carriers as well as for heterozygosity and homozygosity for the G variant in the studied IP group [ 39 ]. The resulting data resemble the findings in some ethnic populations such as those from Japan, Turkey, and America [ 23 , 36 38 ]. For example, Kita et al [ 23 ] report that an incidence of the conversion A → G in the core promoter region of the MT2A gene near the TATA box was 18 % for Japanese people, with the carriage of different genotypes being 82, 17, and 0.9 % for A/A, A/G, and G/G, respectively.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our recent study has also reported a similar prevalence of A by G replacement at position −5 in the core region of the MT2A promoter for homozygous common allele carriers as well as for heterozygosity and homozygosity for the G variant in the studied IP group [ 39 ]. The resulting data resemble the findings in some ethnic populations such as those from Japan, Turkey, and America [ 23 , 36 38 ]. For example, Kita et al [ 23 ] report that an incidence of the conversion A → G in the core promoter region of the MT2A gene near the TATA box was 18 % for Japanese people, with the carriage of different genotypes being 82, 17, and 0.9 % for A/A, A/G, and G/G, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Since the expression of MTs can be affected by genetic variation in the core promoter region and diverse frequency of the essential alleles, the presence of SNPs may lead to reduced cellular activity of metallothioneins and affect abnormal intracellular pathways of cell proliferation, apoptosis, and response to oxidative stress, thus potentially influencing the susceptibility of the individual to various types of tumors [ 6 , 8 , 20 22 , 31 – 33 ]. Unfortunately, among the several previous reports on the rs28366003, rs1610216, and rs10636 SNPs in the MT2A gene, only single studies related to the neoplastic process report the frequency of MT isoforms within different ethnic populations [ 20 23 , 34 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The −5A/G polymorphism has been studied in Japanese and Turkish populations and genotype frequencies of AA, AG and GG are 82, 17 and 0,9 % for Japanese and 87, 12,3 and 0,7 % for Turkish [13, 16]. McElroy et al [17] determined the frequency of the A and G alleles at rs28366003 in the promoter region of MT2A in White and Black females in the Midwestern United States. The frequency of the G allele was 1.1 % for Blacks and 6.4 % for Whites.…”
Section: Resultsmentioning
confidence: 99%
“…The minor allele (G) of rs28366003 is rare in the white population of North America (McElroy et al 2010), and our study included only one homozygote for the minor allele; the association we observed with reduced urinary Cd, Cu, and Zn must be interpreted cautiously. Heterozygotes at rs28366003 also had lower U-Cd than AA homozygotes, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%